1990
DOI: 10.1115/1.2930118
|View full text |Cite
|
Sign up to set email alerts
|

Active Control of Sound Radiation Pressure

Abstract: This paper is concerned with the problem of suppressing the acoustic radiation pressure generated by a structure vibrating in air. The approach is to control the vibration of the modes of the structure most responsible for the radiation pressure. This control is carried out by active means, i. e., by feedback control. As a numerical example, the problem of active control of the far-field radiation pressure generated by the vibration of a simply-supported rectangular elastic plate is considered. The influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…For the SISO configuration, actuator P1 was used in conjunction with PVDF sensor Si as shown in Figure 2. The geometry and location of the PVDF sensor Si is such that it observes only the (1,1), (1,2) and (3,1) modes. Therefore, reduction in the radiation of these modes is observed in Figure 6.…”
Section: Results With Pvdf Error Sensorsmentioning
confidence: 99%
“…For the SISO configuration, actuator P1 was used in conjunction with PVDF sensor Si as shown in Figure 2. The geometry and location of the PVDF sensor Si is such that it observes only the (1,1), (1,2) and (3,1) modes. Therefore, reduction in the radiation of these modes is observed in Figure 6.…”
Section: Results With Pvdf Error Sensorsmentioning
confidence: 99%
“…nn Or, = I (7) Here OJ is the excitation frequency; a. is the modal number; W, is the modal amplitude; and P,, is the modal force depending on the forms of external forces.…”
Section: Lateral Vibration Of Uniform Beammentioning
confidence: 99%
“…Shakers can efficiently control the sound radiation [6][7][8] although they have substantial disadvantages due to their large volume, large weight and support requirements. Recently, the compact distributed types of actuators, such as piezoelectric patches, have been shown to be feasible for structural vibration and acoustic control [9-121. Microphones are generally used as error sensors in ASAC; however, the fact that microphones must be located in the radiated far-field makes them impractical for applications.…”
Section: Introductionmentioning
confidence: 99%
“…Active control has been applied to the control of sound radiation from a plate 1-4 and the sound transmission into a rectangular enclosure. 5, 6 Meirovitch and Thangjitham 4 showed that more control actuators generally gives better control effects. Pan et al 6 used a point-force actuator to control sound transmission into an enclosure, and discussed the control mechanisms in terms of plate-and cavity-dominated modes.…”
Section: Introductionmentioning
confidence: 98%